Persian Medicine Recommendations in Reducing Mental Health Disorders due to Natural Disasters - Marzieh Qaraaty; Jale Aliasl; Malihe Tabarrai (Tehran University of Medical Sciences, 2018)
Throughout history, human has experienced accident and natural disasters such as earthquakes and floods. One of the problems that people encounter after natural disasters is the spiritual and mental complications such as sadness and grief that are inevitable in accidents and disasters and inappropriate treatment leads to physical problems for individuals. The purpose of this study was to evaluate the role of Persian medicine in reducing the spiritual and mortal complications arising from natural disasters. The Persian medicine considers six essential principles (seteyeh zarooriyeh) for keeping health including climate (Ab va Hava), eating and drinking (Khordan va Ashamidan), sleep and wakefulness (Khab va Bidari), body movement and immobility (Harkat va Sokon), retention and excretion of materials (Ehtebas va Estefragh), spiritual and mental moods (Aaraze nafsani). Persian medicine has a special focus on spiritual and mental moods; because they can have a very quick and profound effect on the health of individuals. In the other words, sadness, fear and depression lead to reduction of the body strength and slowness of the refreshing process after natural disaster; while moderate happiness boosts the strengths and increase the life expectancy as well; and makes the work progress faster. Persian medicine scholars have suggested the medical treatments and non-pharmaceutical measures. Medical recommendations include the use of refreshing exhilarating (mofarrehat). One of the non-pharmaceutical measures for the survivors of critical accident to have an active spirit for resuming the life is using influence of the words power of the individuals trusted by the people. The views of Persian medicine scholars can be considered as a good way to improve the spiritual -mental states of injured people from natural disasters and to reduce their therapeutic costs. Conducting clinical studies is recommended in this regard.